Pengaruh Kompleksitas Operasi Perusahaan, Umur Perusahaan dan Opini Auditor Terhadap Ketepatwaktuan Laporan Audit - Nurhairunnisa Nurhairunnisa; Bambang Bambang; Robith Hudaya (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
This study aims to determine the effect of the complexity of company operations, company age, and auditor's opinion on the timeliness of audit reports on mining companies listed on the IDX in 2016-2018. The analysis technique used is descriptive analysis with hypothesis testing using multiple linear regression models through SPSS version 22 software. This study uses secondary data, namely annual reports published on the website www.idx.co.id or published through the company's official website. The population of this research is all mining companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sampling technique was using purposive sampling. Based on predetermined criteria, 30 companies were obtained as samples and 90 observations. The results of this study indicate that there is no influence of the complexity of the company's operations, company age, and the auditor's opinion on the timeliness of the audit report. This research is expected to contribute thoughts, information, and benefits to related stakeholders. For public accountants, this research can be used as a reference that can be used in carrying out their audit service practices, especially in an effort to improve the efficiency and effectiveness of audit implementation through managing factors that can affect the timeliness of submitting audit reports so that audit completion can be improved and accelerated. publication of audited financial reports. For investors, these useful concepts of thought and understanding can be used as a reference in reading and analyzing information in making decisions, especially in matters relating to audited financial reports.